From Natural Scıences to Social Sciences: Organizational Entropy - Demirel, Hatice Gökçe (Arif YILDIZ, 2023)
The laws of thermodynamics are the most fundamental and unshakable laws of natural sciences. Social systems, like natural systems, are subject to entropy, the second law of thermodynamics. Entropy, in natural sciences, means that spontaneous things increase the disorder in the universe. In social sciences, people can create mechanisms that can resist entropy through consciously created structures, usually around a purpose, and processes that facilitate the flow of energy and information between these structures. Organizations create order by giving people a purpose, turning their energy and time into production, and reducing uncertainty with predictable behavioural patterns. However, organizations, like all systems, cannot escape entropy. The aim of the research is to identify at the organizational level the situations that increase and decrease entropy through the elements that create order in organizations (purpose, structure, communication-interaction-information). In this research conducted at the conceptual level, inductive hypotheses were put forward regarding the factors that increase and decrease the entropy of organizations. The lack of overlap between the goals of the upper system of which the organizational goals are a part and the personal goals of the employees who are the subsystem, the degree of formalization, centralization, and the increase in hierarchical role levels increase entropy. The entropy of organizations that can produce and disseminate healthy information from specialization, standardization, interaction of interrelated structures within the system and interaction with the environment is decreasing. These hypotheses regarding the entropy of organizations have a high capacity to produce predictable results at the macro level of analysis. However, as the level of analysis decreases and the complexity of organizations increases, the results may differ within the framework of deterministic chaos theories.

Termodinamik yasaları doğa bilimlerinin en temel ve sarsılmaz yasalarıdır. Sosyal sistemler de doğa sistemleri gibi termodinamiğin ikinci yasası olan entropiye maruz kalmaktadır. Entropi, doğa bilimlerinde kendiliğinden gerçekleşen şeylerin evrendeki düzensizliği artırdığını ifade etmektedir. Sosyal bilimlerde ise genellikle bir amaç etrafında, bilinçli oluşturulmuş yapılar ve bu yapılar arasında enerji ve bilgi akışını kolaylaştıran süreçlerle entropiye karşı koyabilen mekanizmalar oluşturabilirler. Örgütler insanlara amaçla bir yön vererek, enerjilerini ve zamanlarını üretime dönüştürerek, ön görülebilir davranış örüntüleriyle belirsizliği azaltarak bir düzen oluştururlar. Ancak örgütler de tüm sistemler gibi entropiden kaçamazlar. Araştırmanın amacı örgütlerde düzeni oluşturan unsurlar (amaç, yapı, iletişim-etkileşim-bilgi) üzerinden entropiyi artıran ve azaltan durumları örgütsel düzeyde tespit etmektir. Kavramsal düzeyde yapılmış bu araştırmada, örgütlerin entropisini artıran ve azaltan unsurlara ilişkin tümevarımsal hipotezler ileri sürülmüştür. Örgüt amaçlarının parçası olduğu üst sistemin amaçları ve alt sistemi olan çalışanların kişisel amaçlarının örtüşmemesi, resmileştirme, merkezileşme derecesi, hiyerarşik rol basamakların artması entropiyi artırmaktadır. Uzmanlaşma, standardizasyon, sistem içinde birbiriyle ilişkili yapıların etkileşiminden ve çevreyle etkileşiminden sağlıklı bilgi üretebilen ve bu bilgiyi yayabilen örgütlerin entropisi azalmaktadır. Örgütlerin entropisine ilişkin bu hipotezlerin makro analiz düzeyinde öngörülebilir sonuçlar üretme kapasitesi yüksektir. Ancak analiz düzeyi küçüldükçe örgütlerin karmaşıklık düzeyi arttığından deterministik kaos kuramları çerçevesinde sonuçlar farklılık gösterebilir.
DOĞA BİLİMLERİNDEN SOSYAL BİLİMLERE: ÖRGÜTSEL ENTROPİ
Keywords: Strategy; Management and Organisational Behaviour (Other); Strateji; Yönetim ve Örgütsel Davranış (Diğer)